Penerapan Model Auditory, Intellectually, Repetition pada Materi Perubahan Sosial untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas XII IPS 4 SMAN 1 Tengaran: Array - Cirilla Elvi Purwandari (eductum: Jurnal Literasi Pendidikan, 2022)
This study aims to describe the application of the Auditory, Intellectually, Repetition (AIR) model, and to increase student interest and learning outcomes through the application of the Auditory, Intellectual, Repetition model, especially on social change material. The Auditory, Intellectual, Repetition (AIR) learning model is a learning model that combines three aspects, namely auditory (learning by listening), Intellectually (learning by thinking and solving problems) and Repetition (repetition for more effective learning). The research subjects were students of class XII IPS 4 at SMAN 1 Tengaran, Semarang Regency in the academic year 2022/2023. From the results of data analysis showed a significant increase in student interest in learning. This can be seen from the results of observations that the indicators of feeling happy have increased from 72% to 89%, interest in learning from 72% to 88%, attention to learning from 76% to 92% and student engagement increased from 66% to 86%. In addition to increasing interest in learning, the application of the Auditory, Intellectually, Repetition (AIR) model also shows an increase in learning outcomes. The classical completeness level before the action only reached 47%, increased to 74% in cycle 1 and 100% during cycle 2. While the average learning outcomes increased from 71.9 before the action, to 79.9 in cycle 1 and 84.6 in cycle 2